Transitioning from blue growth to the sustainable blue economy: A review of Ireland’s new marine governance in the aquaculture sector - Troya, María Del Camino; Ansong, Joseph Onwona; O’Hagan, Anne Marie (Frontiers in Marine Science, 2023)
This paper reviews the evolution of marine governance in Ireland in response to EU policy requirements in relation to the development of a sustainable blue economy in coherence with the United Nations Ocean Decade (2021-2030). In response to these EU requirements, Ireland has introduced the National Marine Planning Framework (NMPF) and Maritime Area Planning Act, 2021 (MAPA) in 2021 to deliver this sustainable blue economy. This new marine and coastal governance framework in Ireland reforms the consenting regime for key blue economy sectors such as Offshore Renewable Energy (ORE) and sets new policy requirements for the integration of aquaculture within the MSP framework. However, the exclusion of aquaculture from the new consenting regime may hinder the full integration of the sector into MSP and impede compliance with environmental goals established by EU Directives (e.g., WFD, MSFD, MSPD). This review identifies policy and legal gaps which may impede the integration of aquaculture into the new Irish marine governance and national MSP process. Furthermore, this paper analyses aquaculture licensing cases to assess the integration of environmental criteria into planning decisions to gather insight into the readiness of the sector’s transition towards a sustainable model. The analysis from this paper indicates that the legal framework underpinning MSP in Ireland may have a limited impact on the integration of aquaculture and hinder the delivery of sustainability across all marine sectors.